Imagery of the Danube in the Poetry of Taras Shevchenko: Array - Kulchak, Vladyslav (Journal of Danubian Studies and Research, 2020)
The article deals with the research of imagery of Danube River in the poems of Taras Shevchenko. The connection between Ukrainian folklore and the poet’s work is investigated as well.